2013
DOI: 10.1589/rika.28.787
|View full text |Cite
|
Sign up to set email alerts
|

Motion Analysis of Wheelchair Propulsion Movements of Hemiplegic Patients:Effect of a Wheelchair Cushion on the Initiation of Propulsion

Abstract: The objective of this study was to study the effect on the initiation of wheelchair propulsion from stationary sitting when pelvic posterior tilt was inhibited by a wheelchair cushion. [Subjects] The subjects were 18 hemiplegic patients who were capable of sitting in, and propelling a wheelchair. [Method] We used electromyography and a 3D motion analysis system to measure the posterior pelvic tilt angle, the muscle activity of the long head of the biceps femoris (BFLH), and the propulsion speed in the initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We have previously confirmed that wheelchair cushions with anchoring functionality and a removable thigh pad on the driving side are able to suppress posterior pelvic tilt when sitting still, that the period from sitting still until the start of driving is important 3 ) , and that this effect continues until immediately after the start of driving 4 ) . From the above, we considered that it was necessary to investigate adapting wheelchair cushions based on trunk functionality from a single-legged driving motion.…”
Section: Introductionmentioning
confidence: 62%
“…We have previously confirmed that wheelchair cushions with anchoring functionality and a removable thigh pad on the driving side are able to suppress posterior pelvic tilt when sitting still, that the period from sitting still until the start of driving is important 3 ) , and that this effect continues until immediately after the start of driving 4 ) . From the above, we considered that it was necessary to investigate adapting wheelchair cushions based on trunk functionality from a single-legged driving motion.…”
Section: Introductionmentioning
confidence: 62%
“…Thus, the results of anchoring the cushion and removing the thigh pad from the propulsion side in the present study showed results similar to those of the studies by Takeda et al 6 ) , Cron 9 ) , and Engstrom 15 ) . Furthermore, the effect of a wheelchair cushion suppressing pelvic posterior tilt when sitting still as investigated by Kawada et al 12 ) was shown to continue through the third propulsion cycle. We also found that the effect continued through to the third propulsion cycle, and it was possible to quantitatively express the pelvic posterior tilt angle over time.…”
Section: Discussionmentioning
confidence: 95%
“…We assumed that age and sex differences would have a negligible effect on the results. Although such effects are a possibility, previous studies that were mixed sex and that considered a broad range of ages have not reported age or sex differences 11 , 12 ) .…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations